If it's not what You are looking for type in the equation solver your own equation and let us solve it.
78=-6(-5+2n)
We move all terms to the left:
78-(-6(-5+2n))=0
We add all the numbers together, and all the variables
-(-6(2n-5))+78=0
We calculate terms in parentheses: -(-6(2n-5)), so:We get rid of parentheses
-6(2n-5)
We multiply parentheses
-12n+30
Back to the equation:
-(-12n+30)
12n-30+78=0
We add all the numbers together, and all the variables
12n+48=0
We move all terms containing n to the left, all other terms to the right
12n=-48
n=-48/12
n=-4
| 2x-5/7=9x+4 | | 7x-30+4x+18=90 | | 12x+8=26x-52 | | 5x+2(3(x-4)+1)=33 | | 18-6b=-8(3b-7) | | 11x-2=8x+1 | | 4x-1=-7+x | | 180=46-3x(90) | | -8(x+4)=-6x | | -23=7+5w | | -6=2/3-1/3y | | 3(3v+1)=5(-2v-2) | | 9m-9=5m+7 | | O.7n-1.5+7.3n=14.5 | | 6x+3+6x=135 | | 6(x-2)/3=2(x+5)/8 | | 5y+3=9y | | 4x+4+5x-7+17=3x | | 41x=36 | | 0.5(j+2=6 | | 180-x=46-3•(90-×) | | 6(x-2)/3=2(x+5)|8 | | 4(-2p-5)=-68 | | 3X+1=2+2x | | 4x-19=3x-7 | | 2—5=x | | (y*2)*(2*2)=216 | | -2(8x-8)+6x=6(x+5) | | 7−3m=2m+7−5m | | 3x-7=4x+19 | | 5x-3=45x+5 | | 7−3x=2x+7−5x |